2017
DOI: 10.2471/blt.16.180273
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of low birth weight and health outcomes in the first year of life, Ghana

Abstract: ObjectiveTo investigate the effect of birth weight on infant mortality, illness and care seeking in rural Ghana.MethodsUsing randomized controlled trial data, we compared infants weighing 2.00–2.49, 1.50–1.99 and < 1.50 kg with non-low-birth-weight infants. We generated adjusted mortality hazard ratios (aHR), adjusted illness rate ratios (aRR) and adjusted odds ratios (aOR) for health-facility admissions and absence of care seeking for four time periods: infancy, the neonatal period, early infancy and late inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
6
35
0
Order By: Relevance
“…This proportion is similar to that reported (14%) by the literature in low-income countries [21]. Low birth weight may constitute a risk factor of childhood illness, mortality [22] and non-communicable disease (NCDs) such as diabetes and heart disease later in life [23].…”
Section: Birth Weightsupporting
confidence: 88%
“…This proportion is similar to that reported (14%) by the literature in low-income countries [21]. Low birth weight may constitute a risk factor of childhood illness, mortality [22] and non-communicable disease (NCDs) such as diabetes and heart disease later in life [23].…”
Section: Birth Weightsupporting
confidence: 88%
“…Information regarding birth weight is of great importance as it is an indirect indicator of maternal nutrition and predictive indicator of potential neonatal death and malnutrition if the child survives [3]. LBW babies have higher probability of dying within the first month of life or associated with adverse health outcomes like stunted growth [4], delayed motor and social development or learning disabilities [5], lower IQ [6], and high mortality [7]. Also LBW shares higher proportion of global neonatal mortality which is estimated to be around 60-80% [8].…”
Section: Introductionmentioning
confidence: 99%
“…These findings could be an indication that ELBW and VLBW patients may have been unstable and therefore could not be stabilized before a referral or the referrals were not completed [14]. This is supported by a study at Kintampo, Ghana, which revealed an absence of care seeking for babies with a birth weight of 1.50-1.99 kg (AOR, 1.46) compared with infants who did not have a low birth weight [17]. In contrast, studies in Uganda, India, South Africa, and Egypt reported admissions of ELBW infants and a higher proportion of VLBW infants than this study [16,[18][19][20].…”
Section: Discussionmentioning
confidence: 82%